2020
DOI: 10.1186/s12872-020-01541-x
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound imaging of isolated and non aorto-ostial coronary Takayasu arteritis: a case report

Abstract: Background: Isolated coronary Takayasu arteritis is a rare form of ischemic heart disease that typically appears as an aorto-ostial lesion. Although several vascular imaging modalities including ultrasonography, computed tomographic angiography, magnetic resonance angiography or catheter angiography, play crucial roles for diagnosing Takayasu arteritis, the intravascular ultrasound imaging of Takayasu arteritis is not well studied. Case presentation: A 55-year-old woman who was diagnosed with heterozygous fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…However, in the present case, IVUS findings were similar to those of coronary involvement in Takayasu's arteritis, so tocilizumab was used. 5 , 6 This case highlighted that the immunosuppressive drugs such as are effective, and follow-up FDG-PET/CT is useful in monitoring response to immunosuppressive drugs in patients with coronary arteritis even of unknown cause.…”
Section: Discussionmentioning
confidence: 94%
“…However, in the present case, IVUS findings were similar to those of coronary involvement in Takayasu's arteritis, so tocilizumab was used. 5 , 6 This case highlighted that the immunosuppressive drugs such as are effective, and follow-up FDG-PET/CT is useful in monitoring response to immunosuppressive drugs in patients with coronary arteritis even of unknown cause.…”
Section: Discussionmentioning
confidence: 94%
“…Ishiyama et al [ 52 ] reported that IVUS showed that the three-layered structure of the intima, tunica media, and adventitia was not visible, and the vessel was concentrically thickened; unstable plaque and calcification were not seen. Notably, the media was partly unrecognizable, and an echo intensity similar to fibrotic intimal thickening traversed from the intima to the adventitia, making the whole image of the coronary artery unclear [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soto et al [ 36 ] observed typical AP in 62.5% of patients with CAL, atypical AP in 12.5%, and dyspnea in 25%. Shimizu et al [ 43 ] described TAK with isolated CAL in a 55-year-old woman with heterozygous familial hypercholesterolemia who complained of exertional AP.…”
Section: Coronary Artery Lesionsmentioning
confidence: 99%
“…However, there are only individual case reports concerning the application of IVUS in patients with Takayasu arteritis. Takeshi et al reported unrecognized media and the expansion of fibrotic thickening from the media to the adventitia in Takayasu arteritis patients [ 8 ]. Klaus et al reported several hypoechogenicities in the wall of coronary artery [ 9 ].…”
Section: Discussionmentioning
confidence: 99%